2011
DOI: 10.1261/rna.029603.111
|View full text |Cite
|
Sign up to set email alerts
|

Widespread generation of alternative UTRs contributes to sex-specific RNA binding by UNR

Abstract: Upstream of N-ras (UNR) is a conserved RNA-binding protein that regulates mRNA translation and stability by binding to sites generally located in untranslated regions (UTRs). In Drosophila, sex-specific binding of UNR to msl2 mRNA and the noncoding RNA roX is believed to play key roles in the control of X-chromosome dosage compensation in both sexes. To investigate broader sex-specific functions of UNR, we have identified its RNA targets in adult male and female flies by high-throughput RNA binding and transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Thus, it would appear unlikely that UNR would bind to the conserved motif in the tra intron. Nevertheless, the possibility that UNR binds to tra transcripts should not be completely discounted given that UNR binds to many sex-specifically processed transcripts in Drosophila [23].Interestingly, the motif downstream of the most 5′ TRA/TRA2 site shows a partial (7/8 in Chtra ) match to the sequence [(5′-(U/G)GAAGAU(U/A)-3′] suggested by Verhulst et al [11] to be a potential binding site for TRA/TRA2 in Nasonia vitripennis and Apis mellifera . Alignment of the DNA sequences of the 3′ end of the intron identified a conserved type A RBP1 binding site (DCADCTTA) about 100 bp upstream of the splice acceptor site (Figure 4C, purple).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would appear unlikely that UNR would bind to the conserved motif in the tra intron. Nevertheless, the possibility that UNR binds to tra transcripts should not be completely discounted given that UNR binds to many sex-specifically processed transcripts in Drosophila [23].Interestingly, the motif downstream of the most 5′ TRA/TRA2 site shows a partial (7/8 in Chtra ) match to the sequence [(5′-(U/G)GAAGAU(U/A)-3′] suggested by Verhulst et al [11] to be a potential binding site for TRA/TRA2 in Nasonia vitripennis and Apis mellifera . Alignment of the DNA sequences of the 3′ end of the intron identified a conserved type A RBP1 binding site (DCADCTTA) about 100 bp upstream of the splice acceptor site (Figure 4C, purple).…”
Section: Resultsmentioning
confidence: 99%
“…RIP-Seq of Drosophila UNR in male and female flies identified a pronounced sex-specific binding bias for this protein; follow-up RNA-Seq experiments correlated UNR binding with the sex-specific alternative processing of UTRs in target messages [51]. Processing of UTRs, and specially of the 3′-UTR, has been proposed to importantly contribute to global gene expression regulation.…”
Section: Rbps Go ‘Omics’mentioning
confidence: 99%
“…The centrosome and control of mitosis were also significantly enriched terms (n=11). Recent studies identified Csde1 targets in melanoma cells and Drosophila melanogaster 20,36 . Comparison showed that 53 of the 274 transcripts we identified as Csde1-associated transcripts were also identified as a Csde1 target in melanoma cells using iCLIP 20 .…”
Section: Resultsmentioning
confidence: 99%